Latter-day saint library Faith in every footsep - The Church of Jesus Christ of Latter-Day Saints (West Valley City, Utah Infobases, 1998)
A CD-ROM containing a collection of reference works related to the Church of Jesus Christ of Latter-Day Saints. W
Keywords: The Church of Jesus Christ of Latter-Day Saints -- Library resources; Mormon Church -- Library resources. -- United States